THE INFLUENCE OF WORKLOAD AND JOB STRESS ON EMPLOYEE PERFORMANCE AT CONCORD INDUSTRIAL COMPANY - Miranda Desti Fadhila Putri; Sari Marliani; July Yuliawati (Journal Of Resource Management, Economics And Business, 2024)
Purpose: To analyze the influence of workload and work stress on employee performance at PT. Concord Industrial Karawang, a company located in Karawang, known as the "City of Industry" and a hub for global companies like GlobalTech Solutions Research Methodology: This study employed a quantitative descriptive verification method. The population consisted of 110 employees, with participants selected using random sampling. Data analysis was conducted using multiple linear regression through SPSS v.25 software. Results: The results of this study show a partial effect on the workload variable which has a significant effect on employee performance variables. There is a partial effect on the work stress variable which has a significant effect on employee performance. There is a simultaneous effect of workload and work stress together which have a positive and significant effect on employee performance at PT. Concord Industri Karawang. Limitations: The study was confined to PT. Concord Industrial Karawang and may not be generalizable to other industries or regions. The research also focused solely on workload and work stress as factors affecting employee performance, potentially overlooking other influential variables. Contribution: This research provides valuable insights into the relationships between workload, work stress, and employee performance in an industrial setting. The findings can inform management strategies to optimize employee performance by addressing workload and stress factors in similar industrial environments.